The Orexin-A-Regulated Akt/mTOR Pathway Promotes Cell Proliferation Through Inhibiting Apoptosis in Pancreatic Cancer Cells - Suo, Linna; Chang, Xiaocen; Zhao, Yuyan (Frontiers in Endocrinology, 2018)
The peptide orexin-A and its receptor are associated with many physiological processes in peripheral organs and the central nervous system and play important roles in a series of human diseases, including narcolepsy, obesity, and drug addiction. Increasing evidence has indicated high expression of orexin-A and OX1 receptor (OX1R) in malignant tumors, suggesting that the orexin-A/OX1R interaction might be essential for tumorigenesis. Here, we attempted to clarify the correlation between orexin- A expression and malignancy in pancreatic cancer. Our results indicated that the orexin-A/OX1R interaction promotes cell proliferation in pancreatic cancer PANC1 cells. Additionally, orexin-A treatment can protect PANC1 cells from apoptosis, whereas inhibition of the orexin-A/OX1R interaction results in apoptosis through regulating pancreatic cancer cell expression levels of Bcl-2, caspase-9, and c-myc, which are key apoptotic factors. Further investigation revealed that orexin-A treatment activates the Akt/mTOR signaling pathway to promote cell proliferation by inhibiting Bcl-2/caspase-9/c-myc-mediated apoptosis in pancreatic cancer cells. Our findings revealed that the orexin-A/OX1R interaction might be important for tumorigenesis in pancreatic cancer and is a potential target for the treatment of patients with pancreatic cancer.